Effect of Grasses on Native Tree Seedling Establishment Along a Water Stress Gradient: Results of Forest and Greenhouse Experiments - Trinco, Fabio Daniel; Rusch, Veronica Elena; Cardozo, Andrea; Garibaldi, Lucas Alejandro; Tittonell, Pablo Adrian (Wiley, 2024)
Anthropogenic activities such as cattle grazing and forest clearing have led to the establishment of early successional grass layers in some native forests, which may inhibit or entirely prevent native tree regeneration. We hypothesize that increased grass coverage reduces or eliminates the establishment of native tree seedlings by limiting water availability to seeds and seedlings. This study aims to evaluate the impact of grass cover on tree seedling survival under varying levels of soil water stress. We conducted a field experiment using 36 experimental exclosures in two northwest Patagonian valleys, representing a regional gradient in altitude, rainfall, and tree canopy openness. Additionally, a greenhouse experiment was performed with 36 pots, manipulating four levels of grass cover and three levels of water stress. Results from both experiments showed similarities: in the field, the likelihood of finding a live tree seedling was approximately 2.78 times higher in areas without grass compared with grass-covered sites. In the greenhouse, the presence of grass reduced the final number of established seedlings by an average of 43% across all irrigation levels, indicating significant water competition. These findings suggest that management practices promoting grass invasion could severely hinder tree regeneration in forests not adapted to large herbivore intensive grazing. Such situation may be exacerbated in regions suffering water limitation in the growing season or where the climate change would intensify water stress.